Identify The Type of Pleural Effusion with Lung Ultrasound: A Case Report and State-of-Art - Ielo, Simone; Fratini, Antonio; Amante, Edoardo; Spinelli, Marcello (Universitas Brawijaya, 2023)
Pleural effusion is the most common pleural pathology and is seen in a large group of patients admitted to internal medicine wards.The purpose of this state of art literature review is to describe the various ultrasound findings that can be observed, to highlight the ability of lung ultrasound to facilitate differential diagnosis by pointing to a specific type of effusion and its cause.To this end, the clinical case description aims to demonstrate the above and promote the use of bedside lung ultrasound by considering this technique as the fifth physical examination technique after inspection, palpation, percussion and auscultation.